Augmented Features Synergize Radiomics in Post-Operative Survival Prediction and Adjuvant Therapy Recommendation for Non-Small Cell Lung Cancer - Chan, Lawrence Wing-Chi; Ding, Tong; Shao, Huiling; Huang, Mohan; Hui, William Fuk-Yuen; Cho, William Chi-Shing; Wong, Sze-Chuen Cesar; Tong, Ka Wai; Chiu, Keith Wan-Hang; Huang, Luyu; Zhou, Haiyu (Frontiers in Oncology, 2022)
Background Because of the cytotoxic effect, it is challenging for clinicians to decide whether post-operative adjuvant therapy is appropriate for a non-small cell lung cancer (NSCLC) patient. Radiomics has proven promising ability in predicting survival but research on its actionable model, particularly for supporting the decision of adjuvant therapy, is limited. Methods Pre-operative contrast-enhanced CT images of 123 NSCLC cases were collected, including 76, 13, 16 and 18 cases from R01 and AMC cohorts of The Cancer Imaging Archive (TCIA), Jiangxi Cancer Hospital and Guangdong Provincial People’s Hospital respectively. From each tumor region, 851 radiomic features were extracted and two augmented features were derived therewith to estimate the likelihood of adjuvant therapy. Both Cox regression and machine learning models with the selected main and interaction effects of 853 features were trained using 76 cases from R01 cohort and their test performances on survival prediction were compared using 47 cases from AMC cohort and two hospitals. For those cases where adjuvant therapy was unnecessary, recommendations on adjuvant therapy were made again by the outperforming model and compared with those by IBM Watson for Oncology (WFO). Results The Cox model outperformed the machine learning model in predicting survival on the test set (C-index: 0.765 vs 0.675). The Cox model consists of 5 predictors, interestingly 4 of which are interactions with augmented features facilitating the modulation of adjuvant therapy option. While WFO recommended no adjuvant therapy for only 13.6% of cases received unnecessary adjuvant therapy, the same recommendations by the identified Cox model were extended to 54.5% of cases (McNemar’s test p=0.0003). Conclusions Cox model with radiomic and augmented features could predict survival accurately and support the decision of adjuvant therapy for bettering the benefit of NSCLC patients.